Endophytic bacteria Priestia megaterium 170T-4 improves soybean salt tolerance through regulation of ion homeostasis and phytohormone signaling pathways - Hua, Shutian; Liu, Ruiyao; Li, Zhe; Zheng, Han; Zheng, Yanfen; Wang, Youqiang; Zhang, Cheng-Sheng; Wang, Ziyan; Jiang, Mingguo (Frontiers in Microbiology, 2025)
Salt stress in coastal saline-alkali soils impairs plant survival and growth. Plant growth-promoting rhizosphere bacteria (PGPR) and endophytic bacteria can enhance salinity tolerance via stable host associations. This study used culture-based and transcriptomic methods to investigate culturable endophytic bacteria in soybean and their salt-tolerance mechanisms. A total of 154 strains were isolated from the roots of 10 soybean varieties cultivated in coastal saline-alkali soil, spanning 4 phyla, 35 genera, and 76 species. Microbacterium phyllosphaerae and Priestia megaterium were identified as dominant species, from which two representative strains were selected to assess their growth-promoting effects under salt stress. Strain 170T-4 was identified as P. megaterium via multilocus sequence analysis and showed high salt tolerance, growing in up to 6% NaCl. Pot experiments showed that strain 170T-4 significantly improved plant height, root elongation, Na+/K+ homeostasis, proline, and chlorophyll content. Transcriptome profiling and RT-qPCR revealed that strain 170T-4 regulates K+ transport-related genes (GORK and SKOR), ethylene signaling related genes (PTI5, EIN3, and ERF1), and the allene oxide cyclase gene (AOC). Overall, strain 170T-4 improved soybean growth under salt stress by modulating ion transport, osmotic responses, and hormone signaling, showing strong potential as a microbial inoculant for saline-alkali soils.